Factors Affecting Work-Life Balance in Women Academics in Tasikmalaya - Ramadhani, Indi; Indah Bintari, Vivi; Shonia Az Zahra, Qiny (Ann Publisher, 2025)
Background. Work-life balance is something that is highly coveted by female academics. Conditions that allow employees to work optimally in the office and still be able to carry out their personal lives as social beings. The number of female lecturers in Tasikmalaya is increasing from year to year. For female academics, work-life balance is a costly luxury. Obligations as housewives and the need to express themselves outside as female academics need understanding from the campus to facilitate this need. Aims. Based on this description, it is necessary to conduct a study on the factors that affect Work-Life Balance in female academics in Tasikmalaya. Methods. The research method used is a survey method, with data collection techniques using a questionnaire given to female academics in Tasikmalaya as respondents, amounting to 129 of 384 registered at PDDIKTI. Data analysis and hypothesis testing in this study used Multiple Regression Analysis. Result. The research results indicate that emotional intelligence, burnout, work facilities, role conflicts, and commitment to the work-life balance of female academics in Tasikmalaya are influenced simultaneously and partially. Conclusion. Based on the regression equation, work facilities contribute the most to the work-life balance of female academics in Tasikmalaya. This shows that female academics in Tasikmalaya have support in balancing their work lives amid role conflicts and a tendency to experience burnout. Implementation. With the ability to overcome burnout and handle role conflicts that arise with the support of work facilities, emotional intelligence, and high commitment, women academics in Tasikmalaya can still create a work-life balance.